Effects of Tai Chi Chuan on cognitive function in adults 60 years or older with mild cognitive impairment: a systematic review and meta-analysis - Wang, Wen-Ting; Wang, Hong (Frontiers in Physiology, 2025)
BackgroundMild cognitive impairment (MCI) is an intermediate stage between normal aging and dementia. Emerging evidence has demonstrated that mind-body interventions may enhance cognitive function. To elucidate whether stand-alone Tai Chi Chuan (TCC) intervention confers domain-specific benefits on executive function, memory, and global cognition, further investigations should be conducted.PurposeThis systematic review and meta-analysis of randomized controlled trials (RCTs) examined TCC’s effects on global cognition, memory, and executive function, and its duration-response relationship in adults 60 years or older with MCI.MethodsSeven electronic databases were searched for relevant literature, with English as the sole inclusion criterion for language. The methodological quality and risk of bias for all included RCTs were assessed using the Cochrane Risk of Bias (2.0) tool. The pooled effect sizes were evaluated using standardized mean differences (SMD) and 95% confidence intervals (CI). A p-value <0.05 was considered statistically significant.ResultsNine of the 1,442 publications met the inclusion criteria, comprising RCTs involving 1,066 participants (68.95% female) with a mean age of 74.1 (±7.4) years. Long-term TCC demonstrated significant effects on global cognition (p < 0.001; SMD = 0.488; 95% CI: 0.222–0.754), whereas short-term TCC did not (p = 0.172; SMD = 0.682; 95% CI: −0.397–1.660). Overall, TCC showed significant global cognitive benefits (p = 0.003; SMD = 0.526; 95% CI: 0.184–0.869). Long-term memory showed no improvement (p = 0.214; SMD = 0.162; 95% CI: −0.094–0.417), while short-term memory improved significantly (p = 0.021; SMD = 1.010; 95% CI: 0.155–1.865). The overall effect of TCC on memory was significant (p = 0.005; SMD = 0.580; 95% CI: 0.178–0.982). Both short-term and long-term improvements in executive function were significant (p = 0.006; SMD = −0.791; 95% CI: −1.353 to −0.230).ConclusionThe study confirmed TCC’s duration-dependent effects on global cognition in older adults (≥60 years) with MCI. Memory exhibited nonlinear temporal dynamics, characterized by short-term acceleration and long-term plateau, while executive function demonstrated temporal invariance with comparable efficacy across intervention durations.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/home, identifier CRD42024587754.